Effect of intra row spacing on the incidence and severity of pearl millet downy mildew and grain yield - Zarafi, A.B.; Emechebe, A.M. (Informa UK Limited, 2006)
The effect of seven intra row spacing (10, 20, 30, 40, 50, 60, 70 cm) on the incidence and severity of downy mildew of pearl millet and yield components of a local pearl millet variety (Zango) were studied under field conditions in 2002 and 2003 at Samaru, Nigeria. Intra row spacing did not have significant effect on the incidence and severity of the disease but significantly increased plant height, panicle length and weight, 1000-grain weight and grain yield.